Requirements Specification for a web application - Paljakka, Minne (My University, 2018)
This research is part of a software development project that aims to improve an existing web-based business application that is used to access engine technical data per different engine types. The need for a completely new application and development project has occurred, because the organization’s business has evolved and emerged new requirements that go beyond the maintenance of the existing system as the currently used technology is outdated and does no longer support the needed changes. The main intention of this research is to provide a requirements specification for the new improved application, including both the functional and non-functional requirements. Other objectives include giving recommendations for the continuation of the project as well as proposing the technologies and tools to be used in the actual implementation. The research was divided into theoretical and empirical research. In the theoretical part the theory behind the web applications and software engineering were explored, concentrating more in detail on the requirements engineering activity. In the empirical part, the existing application was first inspected, and then the detailed research design was made and executed. In practice, the different stakeholders for the application were identified, and requirements were discovered by utilizing conversational interviews in combination with early prototyping. As a result, the requirements in their raw form were discovered, and finally turned in to the final requirements specification through analysis, representation and validation. Last, the recommendations for the project’s continuation were given. As a main result of this research, a requirements specification for the new enhanced web application was established. The produced specification gives both the functional and non-functional requirements in a prioritized and organized natural language form, but also includes the produced user interface mock-up prototype to provide more visual representation to easy the communication between the different stakeholders. In addition, the research gives recommendations for the web technologies and tools to be used in the implementation of the software, and provides suggestions for the continuation of the development project. Overall, the results will work as an input for the following development activities and give a good base for the project to proceed.
Keywords: Software engineering; web application; requirements engineering; software prototyping; fi=Ohjelmistotekniikka (DI)|en=Software Engineering|; fi=Tietotekniikan koulutusohjelma (DI)|